2008
DOI: 10.3168/jds.2007-0265
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component and Multivariate Analysis of Milk Long-Chain Fatty Acid Composition During Diet-Induced Milk Fat Depression

Abstract: The objective of this study was to assess the relationship between individual milk fatty acids (FA) and diet-induced milk fat depression (MFD) using principal component analysis (PCA) and multivariate analysis (MA). Cow treatment observations (n = 63) from 3 published feeding experiments with lactating dairy cows were used in the analyses. In the PCA, principal component loading plots 1 (PC1) and 2 (PC2) described 55.9% of the total variation in milk FA and fat concentrations. Saturated FA (14:0, 16:0, and 17:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 37 publications
7
62
0
1
Order By: Relevance
“…Of specific importance is a recent study that abomasally infused 43 g/day of trans-10 C18:1 . Although trans-10 C18:1 was incorporated into milk fat at a concentration predicted to decrease milk fat concentration by 0.4 to 0.5 percentage units (Kadegowda et al, 2008), well within the power of the controlled abomasal infusion experiment, there was no effect on milk fat yield, and milk fat concentration was numerically increased by 0.07 percentage units . Likewise, no MFD was observed when the milk fat concentration of trans-10 C18:1 was increased by feeding high-oleic sunflower oil (Hinrichsen et al, 2006).…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 56%
See 2 more Smart Citations
“…Of specific importance is a recent study that abomasally infused 43 g/day of trans-10 C18:1 . Although trans-10 C18:1 was incorporated into milk fat at a concentration predicted to decrease milk fat concentration by 0.4 to 0.5 percentage units (Kadegowda et al, 2008), well within the power of the controlled abomasal infusion experiment, there was no effect on milk fat yield, and milk fat concentration was numerically increased by 0.07 percentage units . Likewise, no MFD was observed when the milk fat concentration of trans-10 C18:1 was increased by feeding high-oleic sunflower oil (Hinrichsen et al, 2006).…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 56%
“…Duodenal flow of trans-10 C18:1 is very dynamic and the maximal reduction in milk fat appears to correspond to a rumen outflow of , 20 to 40 g/day, although much higher outflows can occur, especially in experimental diets that are high in fish oil Shingfield and Griinari, 2007). Likewise, a near-maximal reduction in milk fat yield is observed at a milk fat concentration of , 1.5% to 2.5% trans-10 18:1, although much higher concentrations do occur with certain experimental diets (Loor et al, 2005;Hinrichsen et al, 2006;Shingfield and Griinari, 2007;Kadegowda et al, 2008). Of specific importance is a recent study that abomasally infused 43 g/day of trans-10 C18:1 .…”
Section: Biohydrogenation Intermediatesmentioning
confidence: 98%
See 1 more Smart Citation
“…Principal component analysis of a group of studies showed that t10-18:1 was the isomer most negatively correlated with milk fat (Kadegowda et al, 2008). However, concentration of t10-18:1 does not explain why milk fat content was lower for ground compared with rolled diets, because milk concentrations of t10-18:1 were not affected by processing.…”
Section: Milk Fat Depressionmentioning
confidence: 99%
“…Several studies have associated milk fat depression with increases in milk concentrations of t10-18:1 (Griinari et al, 1998;Kadegowda et al, 2008). In contrast, Lock et al (2007), based on an infusion study, reported that t10-18:1 has no role in milk fat depression (MFD).…”
Section: Milk Fat Depressionmentioning
confidence: 99%